Vector mechanics for engineers., Dynamics /Ferdinand P. Beer, E. Russell Johnston, Jr., with the collaboration of Elliot R. Eisenberg, Robert G. sarubbi. - Beer, Ferdinand P.(Ferdinand Pierre),1915-2003.
Includes index.